Improving General Physical Fitness of High School Students with the Help of Gymnastic Exercises - Kamchiyev Salimberdi Khudaiberdievich (Researchparks Publishing, 2022)
This article reveals the importance of improving the general physical fitness of high school students and preparing students to pass the control test standards of the state educational standard curriculum.